ORGANIZATION OF INDEPENDENT WORK OF STUDENTS ON THE HISTORY OF PEDAGOGY ON THE BASIS OF COMPARATIVE STUDIES - V.V. Sadova (Academy of Cognitive and Natural Sciences, 2009)
The article reveals some peculiarities in organizing and doing students' independent work with the use of some elements of comparative approach.